Arterial remodelling in smokers and in patients with small airway disease and COPD: implications for lung physiology and early origins of pulmonary hypertension. Issue 4 (5th December 2022) - Bhattarai, Prem; Lu, Wenying; Gaikwad, Archana Vijay; Dey, Surajit; Chia, Collin; Larby, Josie; Haug, Greg; Hardikar, Ashutosh; Williams, Andrew; Kaur Singhera, Gurpreet; Hackett, Tillie-Louise; Eapen, Mathew Suji; et al.
Introduction: Pulmonary vascular remodelling in chronic obstructive pulmonary disease (COPD) has detrimental consequences for lung physiology. The aim of our study was to provide a comprehensive size-based morphometric quantification of pulmonary arterial remodelling in smokers and in patients with small airway disease (SAD) or COPD. Method: Movat's pentachrome staining was performed on lung resections for 46 subjects: 12 never-smoker normal controls (NC), six normal lung function smokers (NLFS), nine patients with SAD, nine patients with mild-to-moderate COPD who were current smokers (COPD-CS) and 10 patients with mild-to-moderate COPD who were ex-smokers (COPD-ES). Following a size-based classification of pulmonary arteries, image analysis software was used to measure their number, total wall thickness, individual layer thickness and elastin percentage. Results: All pathological groups showed decreased numbers of pulmonary arteries compared with the NC group in all artery sizes. Arterial wall thickness was greater in NLFS and COPD-CS than in NC. Thickness in COPD-ES was decreased compared with COPD-CS. Intimal thickness was greater in all pathological groups in all arterial sizes than in the NC group. Medial thickness was also greater in small and medium arteries. Intimal thickness of larger arteries in COPD-CS correlated negatively to forced expiratory volume in 1 s/forced vital capacity (FVC) % and forced expiratory flow at 25–75% of FVC. Elastin deposition in small arteries was greatest in COPD-CS. Intimal elastin deposition had a more negative correlation with intimal thickness in NLFS and SAD than in COPD-CS. Conclusion: Smoking, SAD and mild-to-moderate COPD are associated with pruning and a decrease in the number of pulmonary arteries, increased wall thickness and variable elastin deposition. These changes were associated with worse airway obstruction. Pulmonary arterial remodelling occurs in smokers and in patients with small airway disease or COPD, where it affects lung function and may exaggerate pulmonary hypertension. Endothelial-to-mesenchymal transition might be central to these vascular changes. https://bit.ly/3QF5heH